Defamatory post against a beverage brand: A forensic linguistic study - Putu Wahyu Widiatmika (Privietlab, 2026)
A controversial post by an X user regarding the sweetness level of a beverage sparked significant debate on social media. Public opinion was divided; some criticized the user for employing coarse language, while others defended the tweet as a factual description that should be viewed as constructive criticism of the brand. As the tweet could be perceived as offensive to the corporate entity, it raised concerns regarding its potential classification as defamatory speech. This study aims to identify and analyze the defamatory expressions within the tweets by the account from the perspective of forensic linguistics. The primary data source for this study was a specific post regarding a beverage variant from a popular brand in Indonesia. Data collection employed the documentation method utilizing the note-taking technique. Potentially defamatory expressions were analyzed through the theories of syntax, semantics, pragmatics, and discourse. The data were analyzed using a descriptive-qualitative approach. The results indicate that the post specifically targeted the corporate entity, as evidenced by the syntactic construction. Furthermore, the diction and phrasing employed carried pejorative and negative connotations. Although the post stemmed from the user's unpleasant experience after consuming the beverage, it exhibited elements of reputational injury, libel, and insult directed at the company. Consequently, the utterance warranted classification as defamatory speech.